PENGARUH PENERAPAN STRATEGI PEMBELAJARAN KREATIF-PRODUKTIF TERHADAP HASIL BELAJAR MATEMATIKA KELAS XI MIA SMA N 13 PADANG - BETA INDO PUTRA (Jurnal Edukasi dan Penelitian Matematika, 2018)
The problem in learning mathematics is the learning outcomes of students are not optimal. Low learning outcomes occur in class XI MIA SMA N 13 Padang. One of the causes is students  are less active, so that the creativity of students has not been seen in mathematics learning. Creative-Productive learning is one of the learning strategies that can enhance the students activities and learning outcomes . The purpose of this research is to see activities and learning outcomes of students during the application of Creative-Productive Learning Strategies in mathematics lessons. This type of research is quasy-experiment with Randomized Control Group Only Design. The results of this research indicate that the activities of students tend to increase after applying Creative-Productive learning strategies. Based on the analysis of the final test results obtained learning outcomes with the application of Creative-Productive learning strategies better than the learning outcomes of students with conventional learning. It can be concluded that there is an influence the application of Creative-Productive learning strategies to the mathematics learning outcomes.Keywords— Creative-Productive learning, Mathematics Learning, students activities, learning outcomes